MONITORING OF ANTICOAGULANT THERAPY IN PATIENTS WITH DEEP VEIN THROMBOSIS - V. I. Petrov; O. V. Shatalova; A. S. Maslakov; A. V. Kushkinova (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the prevalence of accomplished goal in laboratory clotting parameters for the anticoagulant therapy in deep vein thrombosis (DVT).Material and methods. The study is performed as one-stage, descriptive, analytic, pharmacoepidemiologic investigation. The material for the study were 200 case histories of DVT from Volgograd hospitals. The analyzed were: structure of anticoagulant prescription, coagulogrammes with APTT, prothrombin complex and INR.Results. Direct acting anticoagulants were prescribed in 91% cases. High-molecular heparin was used in 84,5% prescriptions, low-molecular heparins — in 6,5%. Monitoring of APTT was done only in 36% patients. The target values of APTT (1,5–2,5 times higher than upper limit) was reached only in 6% cases. Of the indirect anticoagulants warfarin was used in 75,5%. Although laboratory control of warfarin was done in 97% cases, only in 28% of patients INR at discharge was in the range 2,0–3,0.Conclusion. The data witnesses a variety of drawbacks in anticoagulant therapy of DVT patients. High dosages of HMW heparin and warfarin, not enough rigourous control and dosage titration led to the absence of the desired therapeutic diapasone of hypocoagulation.